2014
DOI: 10.1074/jbc.m113.541474
|View full text |Cite
|
Sign up to set email alerts
|

An Immunogenic Peptide in the A-box of HMGB1 Protein Reverses Apoptosis-induced Tolerance through RAGE Receptor

Abstract: Background:The role of caspase-1 in regulating the immunogenic properties of HMGB1 has not been previously reported. Results: We have mapped a peptide in the A-box of HMGB1 that reverses tolerance through RAGE. Conclusion: Inflammasome signaling regulates the immunogenic activity of HMGB1. Significance: Immunogenic peptides within the HMGB1 A-box may be exploited to reverse immune tolerance in sepsis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 38 publications
1
58
0
2
Order By: Relevance
“…The HMGB1-mediated pyroptosis may then enable the proinflammatory molecules synthesized in the endosomes and cytoplasm to be released extracellularly. The second exciting novel HMGB1-RAGE report by LeBlanc et al (48) describes an additional RAGE-binding epitope in HMGB1 located in the box A domain (binding region sequence 23-50) (48). This observation suggests the possibility that HMGB1 may mediate different biological functions when interacting with RAGE depending on which of the two RAGEbinding epiotopes is involved.…”
Section: Hmgb1 Receptorsmentioning
confidence: 95%
“…The HMGB1-mediated pyroptosis may then enable the proinflammatory molecules synthesized in the endosomes and cytoplasm to be released extracellularly. The second exciting novel HMGB1-RAGE report by LeBlanc et al (48) describes an additional RAGE-binding epitope in HMGB1 located in the box A domain (binding region sequence 23-50) (48). This observation suggests the possibility that HMGB1 may mediate different biological functions when interacting with RAGE depending on which of the two RAGEbinding epiotopes is involved.…”
Section: Hmgb1 Receptorsmentioning
confidence: 95%
“…In line with this, a second binding epitope of HMGB1 to RAGE has been proposed recently. 58 So far, only 1 binding site for HMGB1 on RAGE has been identified, but this was never analyzed with different HMGB1 redox forms. [59][60][61] Whereas 1 of the 2 potential binding sites can be bound similarly by the different HMBG1 redox variants, the other site probably discriminates between the different redox states.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of caspapse 1 activity can diminish HMGB1 release and the inflammatory response during pyroptosis (Kamo et al, 2013; Lu et al, 2012b). In addition, a recent study indicated that HMGB1 at the sites of aa67, aa158, and aa169 can be directly cleaved by caspase 1, but not other caspases (-2, -3, -5, -7, -9 or -11) (Leblanc et al, 2014). Different from full length HMGB1, A box with anti-inflammatory activity, the caspase-1 generated A-box fragment (especially residues 23–50) binding to RAGE can rescue apoptosis-induced immune tolerance in a sepsis model (Leblanc et al, 2014).…”
Section: Hmgb1 Releasementioning
confidence: 99%